Meningkatkan Keterampilan Kolaborasi dengan Menggunakan Model Pembelajaran Kooperatif Two Stay Two Stray (TSTS) pada Pembelajaran IPAS di Kelas V Sekolah Dasar - Tasya Salsabillah; Eko Kuntarto; Issaura Sherly Pamela (Jurnal Kiprah Pendidikan, 2026)
This study aimed to improve fifth-grade students’ collaboration skills through the implementation of the Two Stay Two Stray (TSTS) cooperative learning model. The study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 28 fifth-grade students at SDN 153/IX Suka Makmur. Data were collected through observation and a collaboration skills questionnaire and analyzed using descriptive quantitative methods by calculating percentages and mean scores. The results showed that the average collaboration skill score increased from 65.25% in Cycle I (categorized as “Good”) to 83.25% in Cycle II (categorized as “Very Good”), indicating an improvement of 18%. These findings demonstrate that the Two Stay Two Stray (TSTS) model effectively enhances students’ commitment, participation, deliberation, and mutual respect in group learning activities. Therefore, the TSTS model can be used as an alternative instructional strategy to develop collaboration skills as one of the essential 21st-century competencies in elementary education